School-based support for emotion-related attendance challenges: effectiveness of @School when implemented with neurodiverse adolescents, their parents, and school staff - Karel, Evelyne; Defourny, Cynthia; Keppens, Gil; Graczyk, Patricia A.; Sauter, Floor; Heyne, David (Frontiers in Psychology, 2025)
Emotion-related school attendance challenges (ER-SAC) among neurodiverse adolescents are a growing concern due to their impact on both academic and social–emotional development. Despite the prevalence of ER-SAC, few school-based interventions specifically addressing this challenge have been evaluated in real-world settings. The current effectiveness study examined outcomes of the @School intervention, a modular, developmentally sensitive cognitive behavioral intervention that had previously only been evaluated in a research context. In this study, it was delivered by school-based psychologists in a specialized educational setting. Nineteen neurodiverse adolescents aged 12–17 years, all experiencing ER-SAC, participated in the study along with their parents. @School comprises individualized modules for adolescents and parents, as well as structured collaboration with school staff. Outcomes were assessed at pre-, post-, and five-month follow-up, and included adolescents’ school attendance, anxiety, school-related fear, depression, and self-efficacy, together with parent self-efficacy. Results revealed significant improvements in school attendance, adolescent anxiety (reported by both adolescents and parents), adolescent depression (reported by parents), and school-related fear. No significant changes were observed in adolescent or parent self-efficacy. Post-hoc analyses indicated significant reductions in social anxiety symptoms, although these reductions did not predict school attendance outcomes. Findings support the effectiveness of the @School intervention, delivered in a real-world setting, for improving school attendance and reducing emotional distress among neurodiverse adolescents. The results also highlight the value of school-based interventions that integrate support across multiple levels—addressing the needs of adolescents, their parents, and the school environment—to respond to the complex emotional and contextual factors contributing to ER-SAC.